Predator efficiency reconsidered for a ladybird-aphid system - Kindlmann, Pavel; Yasuda, Hironori; Kajita, Yukie; Sato, Satoru; Dixon, Anthony F. G. (Frontiers in Ecology and Evolution, 2015)
Some experiments indicate that ladybirds can significantly suppress aphid abundance. For example, exclusion of predators by caging aphid-infested plants repeatedly results in higher aphid populations and faster aphid population growth rates. However, aphidophagous ladybirds have never proved effective in controlling aphid populations in the field, which is consistent with the theoretical prediction that long-lived predators cannot be effective in controlling a short-lived prey (the generation time ratio hypothesis, GTR). To resolve this paradox, field experiments, involving two species of ladybirds, Coccinella septempunctata bruckii and Harmonia axyridis were used to determine their efficiency in suppressing populations of the aphid, Aphis gossypii, on small shrubs of Hibiscus syriacus under natural conditions. Instead of by caging, the effect of each ladybird species on aphid population dynamics was determined by removing all the eggs of C. septempunctata from 8 shrubs, those of H. axyridis from a further 8 shrubs, all those of both species from an additional 12 shrubs and leaving the eggs on 6 control shrubs. These predators did not have a negative effect on the peak numbers of the aphids. Thus one should be cautious when interpreting the results of cage experiments, used to assess the efficiency of predators in reducing the abundance of their prey.